Electroluminescence in a rectifying graphene/InGaN junction. Issue 80 (1st November 2017) - Cho, Hak Dong; Yoon, Im Taek; Yuldashev, Sh. U.; Kang, Tae Won; Kim, Deuk Young; Lee, Jong-Kwon
Abstract : A graphene-InGaN Schottky junction has been successfully fabricated by transferring graphene layers onto n-type In0.23 Ga0.77 N/GaN/Al2 O3 substrates. Abstract : A graphene-InGaN Schottky junction has been successfully fabricated by transferring graphene layers onto n-type In0.23 Ga0.77 N/GaN/Al2 O3 substrates. Current–voltage ( I – V ) measurement across the junction demonstrates the rectifying behaviour. Temperature dependent I – V characteristics in a range of 10 K to 300 K reveal that the charge transport mechanism is dominated by thermionic emission. Also, it is observed that the charge-transfer induced variation of Fermi energy of graphene affects the flow of current. This graphene/InGaN junction shows electroluminescence (EL) characteristics under a forward bias, producing bright blue emission (430 nm) at room temperature. As the temperature increases, the EL peak is shifted to a lower energy with a reduced peak intensity due to the increased nonradiative recombination rate. The dependence of EL intensity on the current of the graphene/InGaN junction confirms the band-to-band recombination mechanism in the InGaN layer by the bimolecular radiative recombination. Therefore, the observed results provide an insight for implementing graphene based Schottky-junction devices with tunable emission by utilizing the variable bandgap of the InGaN layer.